Emerging evidence of an effect of salt on innate and adaptive immunity. Issue 12 (5th December 2018) - Evans, Rhys D R; Antonelou, Marilina; Henderson, Scott; Walsh, Stephen B; Salama, Alan D
Abstract: Salt intake as part of a western diet currently exceeds recommended limits, and the small amount found in the natural diet enjoyed by our Paleolithic ancestors. Excess salt is associated with the development of hypertension and cardiovascular disease, but other adverse effects of excess salt intake are beginning to be recognized, including the development of autoimmune and inflammatory disease. Over the last decade there has been an increasing body of evidence demonstrating that salt affects multiple components of both the innate and adaptive immune systems. In this review we outline the recent laboratory, animal and human data, highlighting the effect of salt on immunity, with a particular focus on the relevance to inflammatory kidney disease.